Synthesis and characterization of fluorosulfonyl imide isatin biphenylene block copolymer for PEMFC. (28th June 2018) - Ryu, Taewook; Chandra, Sabuj Sutradhar; Ahmed, Faiz; Lopa, Nasrin Siraj; Yoon, Soojin; Yang, Hanmo; Lee, Seungchan; Choi, Inhwan; Kim, Whangi
Abstract: In this study, A fluorosulfonyl imide-containing precursor derived from fluorosulfonyl isocyanate was synthesized and grafted on poly (isatin-biphenylene) random and block copolymers. The carbon-carbon structured poly (isatin biphenylene)s were prepared by super acid catalyzed polyhydroxyalkylation reaction with istain, 2, 2′-biphenyl, 2, 2′-dihydroxybiphenyl. A fluorosulfonyl imide-containing precursor was prepared from chlorosulfuric acid and fluorosulfonylisocyanate. Fluorosulfonyl imide group have higher acidity than sulfonic acid group, therefore the membranes containing fluorosulfonyl imide groups instead of sulfonic acid groups were studied. These membranes showed slightly higher performance of proton conductivity, low water uptake, and good dimensional stability. The structure of the synthesized polymer was investigated by 1 H NMR spectroscopy. Surface morphologies will also be assessed by atomic force microscope (AFM). Microphase-separated block copolymers are preferred over random copolymers. Graphical abstract: Random and block copolymers successfully synthesized from isatin, biphenyl and 2.2′-biphenol with super acid catalyst. Block copolymer membranes show higher proton conductivity than random copolymers. The block copolymer showed the IEC value 1.45 meq./g, water uptake 19.14% and the proton conductivity 78.89 mS/cm at 80 °C under 90% RH. Block copolymer membrane showed a greater dependence of proton conductivity on the relative humidity, and had higher conductivity and cell performance than that of random copolymer with similar IEC value. These results showed that the morphology of polymer matrix greatly affected the cell performance and membrane with well-separated hydrophilic/hydrophobic phase is very important in the fuel cell application. This research demonstrated the possibility of promising BPIIB membranes for excellent proton conductivity and cell performance. Highlights: Block and random copolymers were synthesized from biphenyl, 2, 2′-biphenol and isatin via super acid catalyzed. Fluorosulfonyl imide super strong acid was grafted on copolymers instead of sulfonic acid. Block copolymer showed better proton conductivity, physical, and chemical stability than random copolymer. Block copolymer showed the IEC and water uptake value 1.45 meq./g and 19.14% respectively.